The onshore-offshore variablity of zooplankton diversity and abundance during the summer seson along the Kuroshio current, East of Taiwan. - Parrenas, Hannah Jane S.
The north-flowing oligotrophic Kuroshio Current highly influences physicochemical, and biological productivity. With few studies focusing on the zooplankton community in eastern Taiwan, it limits absolute comprehension of the response of biological structures on the Kuroshio that could further contribute to the understanding of the Kuroshio Paradox. Physicochemical data and zooplankton samples from the KTV1 transect between 121.7° E and 123° E at 23.8° N in June 2015 (i.e., summer season) were collected to better understand the impact of Kuroshio on zooplankton. Results showed the typical hydrographical characteristic of Kuroshio (high temperature and salinity), and the enhancement of Chl a in shallow onshore stations as attributed to the uplifting of nutrient concentrations up to 50 m depth. Co-inertia analysis revealed abundance of zooplankton in the onshore stations highly correlated with Chl a, nutrient concentrations, and salinity were significantly different from the offshore stations (p=0.004). Temperature exhibited no influence on the spatial and temporal patterns in the KTV1 transect. The zooplankton diversity however did not exhibit significant differences (p=0.113). The zooplankton morphospecies dominating during the summer include the Calanoida, Cyclopoida, Appendicularia, Ostracod, Copepoda nauplii, Chaetognatha, Pteropoda, Harpacticoida, Doliolida, and Polychaeta. This study provides a new perspective on the response of the zooplankton community to the Kuroshio Current. It also highlights the important role of coastal uplifting in predicting the abundance and distribution of the zooplankton.